2023
DOI: 10.1002/adem.202201842
|View full text |Cite
|
Sign up to set email alerts
|

Parrot Beak‐Inspired Metamaterials with Friction and Interlocking Mechanisms 3D/4D Printed in Micro and Macro Scales for Supreme Energy Absorption/Dissipation

Abstract: Energy absorption and dissipation features of mechanical metamaterials have widespread applications in everyday life, ranging from absorbing shock impacts to mechanical vibrations. This article proposes novel bioinspired friction‐based mechanical metamaterials with a zero Poisson's ratio behavior inspired from parrot's beaks and manufactured additively. The mechanical performances of the corresponding metamaterials are studied at both macro and micro scales by experiments and finite element analysis (FEA). An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The samples were clamped by a pair of jigs, with one end fixed and the other end stretched by a moving stage driven by a screw slide. To avoid being affected by dynamic responses, the kirigami samples were stretched at a low speed of 5 mm/min (in accordance with the standard ASTM D638-14 [ 64 ], using the same testing speed as that used in quasi-static testing in previous studies [ 47 , 65 ]) until they broke. We used a load cell (SBT-673, SIMBATOUCH, Guangzhou, China) to measure the force generated during stretching, and a laser distance sensor (HG-C1200, Panasonic, Kadoma, Osaka, Japan) to measure the displacement of the screw slide.…”
Section: Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were clamped by a pair of jigs, with one end fixed and the other end stretched by a moving stage driven by a screw slide. To avoid being affected by dynamic responses, the kirigami samples were stretched at a low speed of 5 mm/min (in accordance with the standard ASTM D638-14 [ 64 ], using the same testing speed as that used in quasi-static testing in previous studies [ 47 , 65 ]) until they broke. We used a load cell (SBT-673, SIMBATOUCH, Guangzhou, China) to measure the force generated during stretching, and a laser distance sensor (HG-C1200, Panasonic, Kadoma, Osaka, Japan) to measure the displacement of the screw slide.…”
Section: Experimental Setupmentioning
confidence: 99%
“…Its semi-crystalline structure provides well-balanced mechanical properties, with the crystalline regions contributing to its rigidity, yield strength, creep resistance, chemical resistance, and melt temperature, while the amorphous regions provide impact resistance, permeability, thermal expansion, and elastic properties [ 46 ]. In the study conducted by Hamzehei et al (2023), it was demonstrated that the use of PA12 material in 3D printing of metamaterials resulted in remarkable recoverable behavior and exceptional energy absorption and dissipation properties [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…A common strategy is to use magnetic inclusions in the system to achieve structural stiffness control [18][19][20]. Hamzehei et al [21] analyzed a new type of bionic friction mechanical metamaterial with zero Poisson's ratio from both macro and micro aspects, and carried out 3D printing and research at the micro level, showing good energy absorption and dissipation properties. Yao et al [22] proposed a new type of metamaterial plate (metaplate) composed of a new type of phononic crystal unit, and verified the complete vibration isolation of the complete 3D phononic bandgap in a certain frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to auxetic behaviour, there are many other artificial mechanical behaviours like negative stiffness, negative compressibility, and ultra-lightweight ultra-high stiffness properties that are achievable through different types of mechanical metamaterials [10,13]. Such properties are controllable by tuning the unit-cell geometry through several methods like computer-aided design (CAD) and topology optimisation [12,14,15] Due to this unique behaviour, auxetics have been considered for different applications such as prosthetics [16], tissue engineering [17], sports practice [18], textile industry [19], biomechanical [20], vibration isolation [21] and enhanced thermo-mechanical applications [22]. Silva et al [23] presented a comprehensive review on the chemical composition, and physical and mechanical properties of the cork material and signified its products and sub-products.…”
Section: Introductionmentioning
confidence: 99%